Quantitative Trait Loci Analysis for Kernel‐Related Characteristics in Common Wheat (Triticum aestivum L.). Issue 4 (1st July 2015) - Li, Meixia; Wang, Zhulin; Liang, Ziying; Shen, Weinan; Sun, Fengli; Xi, Yajun; Liu, Shudong
ABSTRACT: This study aimed to identify quantitative trait loci (QTL) controlling wheat ( Triticum aestivum L.) 1000‐kernel weight (TKW), kernel size (KZ), and kernel shape (KS), using F2 and F2:3 populations derived from a cross between lines '0911–46' and '42'. F2:3 grown in two different environments and two parents and F2 plants grown in one environment were phenotyped and genotyped for TKW, KZ including kernel length, kernel width and kernel thickness; and KS (ratios of kernel width/kernel length and kernel thickness/kernel length). Quantitative trait locus investigation was conducted based on a linkage map with 176 simple sequence repeat markers by composite interval mapping. A total of 53 QTLs (logarithm of odds ≥ 3) were identified on 13 chromosomes for six evaluated traits. Of these 53 QTL, six for TKW were located on chromosomes 1A, 2A, 2B, and 2D; 27 for KZ were on chromosomes 1A, 2D, 3A, 4D, 5A, 5B, 6D, and 7B; and 20 for KS were on chromosomes 1A, 1B, 2B, 2D, 3B, 4D, 5A and 7D. Two stable gene clusters influencing TKW, KZ, and KS were detected on chromosomes 1A and 2D, respectively. The QTL for TKW were located mainly on the A genome and the QTL for KS were mainly on the B genome, whereas the QTL for KZ were evenly distributed on the A, B, and D genomes. The QTLs for TKW and KS were mainly on homologous Group 1 and Group 2, whereas the QTL for KZ were evenly distributed on the seven homologous groups.